Nurse Fatigue and Nurse, Patient Safety, and Organizational Outcomes: A Systematic Review. (December 2021) - Cho, Hyeonmi; Steege, Linsey M.
Hospital nurses are at high risk of fatigue due to stressful work environments with heavy workloads and non-standard work schedules. This systematic review examined the relationship between hospital nurse fatigue and outcomes. Full-text English language quantitative studies published between January 2000 and July 2020 were included. A total of 22 articles were reviewed and synthesized. The findings were synthesized into three major categories: nurse outcomes, nurse-reported patient outcomes, and organizational outcomes. Some of the most commonly studied outcomes include nursing performance (n=3), sickness absence (n=3), and intention to leave (n=4). Fatigue was consistently associated with mental health problems, decreased nursing performance, and sickness absence. Many studies confirmed that nurse fatigue is negatively associated with nurse, patient-safety, and organizational outcomes. However, our findings highlight gaps in current knowledge and the need for future research using a longitudinal design and measuring additional outcomes to better understand the consequences of nurse fatigue.